The Influence of Organizational Citizenship Behavior and Work-Life Balance on Employee Performance: The Mediating Role of Work Motivation - Ramadhan, Fatkhurrozaq; Fitriati, Azmi; Harianto, Eko; Widhiandoro, Hengky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of Organizational Citizenship Behavior and Work-Life Balance on Employee Performance of Pondok Pesantren Modern Zamzam Muhammadiyah Cilongok, with work motivation as a mediating variable. This research is quantitative in nature, using primary data taken by distributing questionnaires. The population of this study was 311 people using the studied sampling technique. The results of this study indicate that organizational citizenship behavior has no significant and positive effect on employee performance, work-life balance has a significant and positive effect on employee performance, organizational citizenship behavior has a significant and positive effect on work motivation, work-life balance has a significant and positive effect on work motivation, organizational citizenship behavior has a significant and positive effect on performance, work motivation has an effect through work motivation, and work-life balance has a significant and positive effect on employee performance through work motivation.